Strategi Guru Pendidikan Agama Islam dalam Implementasi Pembelajaran Ramah Anak di Sekolah Dasar Negeri (SDN) Megaluh Jombang - Arifin, Arifin; Solichin, Mujianto; Maftuhatin, Lilik; Nudin, Wahyu Rifwan (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
Education is a process of changing the attitudes and behavior of a person or group of people in an effort to mature humans through teaching and training. Islamic Religious Education is a conscious effort made by teachers in order to prepare them. In education, strategy means an outline of the direction that is carried out or taken to achieve a predetermined target. Teachers as sources who provide teaching and students as objects who gain knowledge. In this research, qualitative methods are used, where researchers want to get results directly from what happens in the field. The main objective is to find out the strategies of Islamic Religious Education teachers in Megaluh state elementary schools, as well as how to implement child-friendly learning in these schools, along with supporting and inhibiting factors in the implementation of learning. The methods used include field observations, interviews and existing documentation. And the results of the implementation of child-friendly learning at the Megaluh State Elementary School have gone well. This can be seen from well-structured learning, the teacher is the main supporter in achieving the expected learning goals.